Zur Bewertung von Schätzungen bei der gewöhnlichen Regressionsanalyse - Jahn, Johannes (Metrika, 1981)
In this paper the multiple regression analysis is considered. The regression coefficients obtained by this method are examined with respect to their numerical stability. With simple stability considerations a criteria is given which can be used if an estimator is to evaluate. © 1981 Phydica-Verlag.
UnivIS-Import:2015-03-05:Pub.1981.nat.dma.pama21.zurbew